1998
DOI: 10.1016/s0168-6445(98)00002-3
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding-cassette (ABC) transport systems: Functional and structural aspects of the ATP-hydrolyzing subunits/domains

Abstract: Members of the superfamily of adenosine triphosphate (ATP)-binding-cassette (ABC) transport systems couple the hydrolysis of ATP to the translocation of solutes across a biological membrane. Recognized by their common modular organization and two sequence motifs that constitute a nucleotide binding fold, ABC transporters are widespread among all living organisms. They accomplish not only the uptake of nutrients in bacteria but are involved in diverse processes, such as signal transduction, protein secretion, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
153
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(159 citation statements)
references
References 91 publications
(164 reference statements)
3
153
0
3
Order By: Relevance
“…Assuming that Rad50's ATP binding is required for chromatin association, we postulate that the rad50-14 mutation causes the ATPase motif to become stuck in an ATP-bound conformation and that this allows both association of the MRN complex with chromatin and partial DSB processing (Acharya et al 2008), but inhibits detachment of the MRN complex from chromatin, by preventing ATP hydrolysis. This hypothesis corresponds with results by others that have shown that mutations in the conserved Walker B motif aspartate residue abolish ATP hydrolysis but may or may not disrupt ATP binding (Frelet and Klein 2006;Koronakis et al 1995;Panagiotidis et al 1993;Schneider and Hunke 1998;Shyamala et al 1991).…”
Section: Immunolocalizationsupporting
confidence: 90%
“…Assuming that Rad50's ATP binding is required for chromatin association, we postulate that the rad50-14 mutation causes the ATPase motif to become stuck in an ATP-bound conformation and that this allows both association of the MRN complex with chromatin and partial DSB processing (Acharya et al 2008), but inhibits detachment of the MRN complex from chromatin, by preventing ATP hydrolysis. This hypothesis corresponds with results by others that have shown that mutations in the conserved Walker B motif aspartate residue abolish ATP hydrolysis but may or may not disrupt ATP binding (Frelet and Klein 2006;Koronakis et al 1995;Panagiotidis et al 1993;Schneider and Hunke 1998;Shyamala et al 1991).…”
Section: Immunolocalizationsupporting
confidence: 90%
“…This region is known collectively as the H-loop [44] and corresponds approximately to a region earlier referred to as the switch region [7]. Comparison of the Xray structures of ABC NBDs reveals that the position of the histidine, and of the immediately downstream helix 7, is quite variable with respect to the central b sheet of the nucleotide-binding core, with this region appearing to pivot about Ca atoms at its N-and C-termini, a notion supported by our MD simulations of HisP, which reveal hinges at these points [55].…”
Section: What Is the Role Of The Conserved Active Site Histidine?mentioning
confidence: 99%
“…The ATP-binding cassette (ABC) superfamily comprises systems sharing common characteristics (Schneider and Hunke 1998). ABC systems are present in prokaryotes and in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…These were identified by comparing the predicted secondary structure of some ABC modules to the known three-dimensional structure of ATPhydrolyzing enzymes. These are the Switch region, named by analogy to a sequence in the RecA protein that was proposed to play a role in the propagation of conformational changes triggered by ATP hydrolysis, and some residues distal to the Switch region for which little functional information is available (Mourez et al 1997;Schneider and Hunke 1998).…”
Section: Introductionmentioning
confidence: 99%